The design of seed storage facilities for genetic conservation - Cromarty, A.S.; Ellis, R.H.; Roberts, E.H. (1982)
This is an in-depth report of the factors to be taken into consideration when designing seed storage facilities for genetic conservation. (Revised 1990). Also in Chinese